English as an index of neoliberal globalization: The linguistic landscape of Nur-Sultan, Kazakhstan. (July 2022) - Manan, Syed Abdul; Hajar, Anas
Abstract: Examining the linguistic landscape of the new capital city of Kazakhstan, Nur-Sultan (formerly Astana), this article demonstrates the sociolinguistic transformations following adoption of neoliberal economic policies during the post-Soviet period. The study uses 'neoliberal governmentality' as a conceptual lens to examine how neoliberalism as an economic policy evolves into a form of governance reinforcing the logic of the market in peoples' linguistic behaviors. Drawing on a photographic survey of the linguistic landscape and ethnographic interviews, the study shows that liberalization and flexibilization of the linguistic market has allowed English and Latinized brand names in several foreign languages to occupy a substantial space, frequency, and prominence in the LL. English appears to challenge the decades old dominance of the Russian language as it evidently wields remarkable visibility as the most valued marketing tool. Glimpses of Latinized Kazakh signboards indicates a gradual bottom-up shift to Latinization of the Kazakh language. By situating language as a socially grounded practice, ethnographic analysis of linguistic landscape can provide valuable theoretical insights about different manifestations of neoliberalism, particularly showing how neoliberal governmentality shapes mental linguistic hierarchies, mobilizing peoples' subjectivities to associate language (s) with the quality of goods/products, their prices, bargaining strategies, lifestyles, and social standing. Highlights: A liberalized linguistic market has allowed English and Latinized brands names to spread in the LL. English appears to challenge the decades old dominance of the Russian language. Latinized Kazakh signboards indicates a bottom-up shift to Latinization. Ethnography of linguistic landscape enables to capture forms of neoliberalism.